2020
DOI: 10.3390/nu12082247
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomic Profile of Preterm Infants Receiving Human Milk with Either Bovine or Donkey Milk-Based Fortifiers

Abstract: Fortification of human milk (HM) for preterm and very low-birth weight (VLBW) infants is a standard practice in most neonatal intensive care units. The optimal fortification strategy and the most suitable protein source for achieving better tolerance and growth rates for fortified infants are still being investigated. In a previous clinical trial, preterm and VLBW infants receiving supplementation of HM with experimental donkey milk-based fortifiers (D-HMF) showed decreased signs of feeding intolerance, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…In the present study, citric acid was found to share a common metabolic fate through time, as its levels increased with age in both groups (3rd month compared to the 3rd day), as supported by Figure 3 and Figure 4 . In accordance with our results, a previous clinical intervention with subjects receiving bovine or donkey breast milk indicated citric acid as a maturation biomarker for this group [ 52 , 58 ]. However, citric acid is also a key compound of the metabolic excretion profile during the first days (1st to 7th day) of life in BF infants [ 1 , 52 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, citric acid was found to share a common metabolic fate through time, as its levels increased with age in both groups (3rd month compared to the 3rd day), as supported by Figure 3 and Figure 4 . In accordance with our results, a previous clinical intervention with subjects receiving bovine or donkey breast milk indicated citric acid as a maturation biomarker for this group [ 52 , 58 ]. However, citric acid is also a key compound of the metabolic excretion profile during the first days (1st to 7th day) of life in BF infants [ 1 , 52 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…Variations in the levels of citric acid produced during the tricarboxylic acid (TCA) cycle are affected by factors related to gestational age, lactation, height, weight, growth rate and energy demands of the newborn [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of DF also reduced the frequency of gastroesophageal reflux in infants showing clinical signs of gastroesophageal reflux and cardiorespiratory symptoms associated to feeding intolerance [ 37 ]. A recent urinary metabolomics investigation revealed that the different quality of the nutrients provided resulted in different urinary metabolic patterns [ 38 ]. Moreover, we also reported that DF- and BF-arms had similar short-term growth outcome as well as long-term auxological and neurodevelopmental outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In an ancillary study, the use of DF reduced also the gastroesophageal reflux frequency in infants showing infants with clinical signs of gastroesophageal reflux and cardiorespiratory symptoms associated with feeding intolerance [27]. A recent urinary metabolomics investigation revealed that the different quality of the nutrients provided by isocaloric and isoproteic fortification with either DF and BF resulted in different urinary metabolic patterns [28].…”
Section: Introductionmentioning
confidence: 99%